AHP-COPRAS untuk Pemeringkatan Ketersediaan Fasilitas Kesehatan di Indonesia - Wibisono, Setyawan; Hadikurniawati, Wiwien; Almin, Imam Husni Al (LPPM UNIKA Santo Thomas, 2023)
In handling Covid-19, health resources are one of the factors that play a very important role in reducing the death rate. For this reason, we offer a study on the topic of ranking the availability of health resources in handling the Covid-19 pandemic in provinces in Indonesia using the AHP (Analytical Hierarchy Process) and COPRAS (Complex Proportional Assessment) hybrid methods. The use of the pairwise comparison matrix as a method for testing the validity of the weights for each criterion produces a weight value of 0.363760164 for the criteria for the number of doctors per population and the criteria for the number of nurses per population, a weight value of 0.1588353 for beds per 1000 people, a weight value of 0, 075333696 for the number of hospitals per population, and a weight value of 0.038310676 when going to the hospital. This ranking system places DKI Jakarta first with a utility value of 100%, while the second rank is the Special Region of Yogyakarta with a utility value of 63.59. There is a considerable gap compared to other provinces in terms of the availability of health resources in handling the Covid-19 pandemic. The availability of health facilities in DKI Jakarta is quite far when compared to other provinces in terms of the availability of health resources in handling the Covid-19 pandemic. DKI Jakarta remains the area with the most excellent health facilities.